The influence of social networks on the development of addiction in adolescents - Martinović, Biljana; Sinanović, Šćepan; Sekulić, Jelena; Potić, Srećko; Subotić, Slobodan; Babić, Vukan; Bubanj, Saša (PONS - medicinski časopis, 2024)
The rate of adoption of new technologies has been increased drastically with the development of civilization, and some research shows that media are generally adopted faster than other forms of new technologies. In this sense, the Internet has become a global phenomenon in a short period of time. A significant place in the variety of interactive communications on the Internet is occupied by social networks. They become an inevitable way to communicate, make contact, follow events and connect with the environment. Social networks such as Tik Tok, Instagram, Snapchat, Facebook, Twitter, YouTube and many others have escalated into imperative usage, especially among young people. These are specific online communities, where users (especially young people) try to create their profiles in a creative and fun way, start communication, and some individuals also try make money. In the last few years, the question of the real consequences of computer usage and the Internet usage especially by children, has become a new and very dynamic area of ​​research. A large number of documents are being written about the consequences of using these innovations on the intellectual, emotional and social development of children, adolescents and adults. The work of a nurse as a member of a team in the prevention of addiction to the Internet and social networks is extremely important, especially in the field of counseling, which refers to a wide range of technically simpler psychological therapies, from giving advice, through compassionate listening to young people struggling with depressive disorders, to structured ways encouraging young people to solve problems. The work of a nurse as a member of a team in the prevention of addiction to the Internet and social networks is extremely important, especially in the field of counselling, which refers to a wide range of technically simpler psychological therapies, from giving advice, through compassionate listening to young people struggling with depressive disorders, to structured ways of encouraging young people to solve problems. The aim of this paper is to consider the influence of social networks on the development of depression in adolescents, as well as the importance of nurses as educators of young people in the prevention of depressive disorders. In the paper is used a descriptive method in order to consider the influence of social networks on the development of depression in adolescents, as well as the role and importance of the nurse in educating young people about the risks of inappropriate use of social networks.